Understanding the Role of the Otolaryngology Hospitalist: Tracheostomies and Tracheostomy Care. (September 2022) - Issa, Mohamad; El-Kouri, Nadeem; Mater, Sara; Lee, Jonathan Y.; Snyderman, Carl; Lee, Yan
Introduction: The concept of a hospitalist has been well established. This model has been associated with reduced length of stay contributing to reduction in healthcare costs. Minimal literature is available assessing the effects of an otolaryngology (ENT) hospitalist at a tertiary medical center. The aim of this study is to assess the role of an ENT hospitalist on (1) performing tracheostomies and (2) providing care as part of the tracheostomy care team (TCT). Methods: Retrospective chart review of all tracheostomies performed by the ENT service over 2 years (July 2015-June 2017), and prospective data collection of all tracheostomy care consults over 1 year (July 2016-June 2017). In year 1 (from July 2015 to June 2016), no ENT hospitalist was employed, and in year 2 (from July 2016 to June 2017), an ENT hospitalist was employed. Results: Compared to other Ear, Nose, and Throat (ENT) surgeons, the ENT hospitalist performed tracheostomies with shorter patient wait times, and performed a greater proportion of percutaneous tracheostomies at the bedside versus open tracheostomies in the operating room. The tracheostomy care team (TCT) received 91 consults over the course of 1 year with an average of 1.1 billable procedures generated per consult. Conclusion: In this study, an ENT hospitalist was decreased patient wait time to tracheostomy and increased bedside percutaneous tracheostomies, which has positive implications for resource utilization and healthcare cost. The average wait time to receive a tracheostomy was reduced when calculated across the entire department due to the availability of the ENT hospitalist to see and perform tracheostomies. The TCT generated many billable bedside procedures in addition to encouraged decannulation of patients. This study highlights the fact that the ENT hospitalist contributes to providing expedient tracheostomies and provides valuable consulting services as part of a TCT at a high-volume tertiary care facility.